Kinematic analysis of the tennis serve in young tennis players - Durovic, N.; Lozovina, V.; Pavicic, L.; Mrdulias, D. (Acta Kinesiologica, 2008)
Tennis serve is one of the most important elementary techniques that make a tennis player successful. Model that analyzes optimal technique of tennis serve was constructed based on analyses of professional ATP players and it was used in this research as well. The purpose of this study was to identify if young tennis players who have been professionally active between 1-3 years of trainings are using serve technique in the right way and if there are any differences in their practice compared to "Kinetic Service New MODEL" that we represented in previous work. For this research we used 63 young tennis players between 7-9 years old that had one, two or three years of experience. In order to see if the serve is correctly or incorrectly performed they ware analyzed through sophisticated 3-D Motion Analysis System with accompanying Software. Results of analyses show us that none of these young tennis players are able to serve correctly. Results also tell us that through "Kinetic Service New MODEL" their OCG movement while serving is totally different from the OCG movement within professional players, and that also certain actions that professionals do while serving in succession, young players could not demonstrate.